Simultaneous biomonitoring of volatile organic compounds' metabolites in human urine samples using a novel in-syringe based fast urinary metabolites extraction (FaUMEx) technique coupled with UHPLC-MS/MS analysis. (July 2023) - Gurrani, Swapnil; Prakasham, Karthikeyan; Huang, Po-Chin; Wu, Ming-Tsang; Wu, Chia-Fang; Lin, Yu-Chia; Tsai, Bongee; Krishnan, Anbarasu; Tsai, Pei-Chien; Ponnusamy, Vinoth Kumar
Abstract: Assessing the impact of human exposure to environmental toxicants is often crucial to biomonitoring the exposed dose. In this work, we report a novel fast urinary metabolites extraction (FaUMEx) technique coupled with UHPLC-MS/MS analysis for the highly sensitive and simultaneous biomonitoring of the five major urinary metabolites (thiodiglycolic acid, s-phenylmercapturic acid, t, t-muconic acid, mandelic acid, and phenyl glyoxylic acid) of common volatile organic compounds' (VOCs) exposure (vinyl chloride, benzene, styrene, and ethylbenzene) in human. FaUMEx technique comprises of two-steps, liquid-liquid microextraction was performed first in an extraction syringe using 1 mL of methanol (pH 3) as an extraction solvent and then, the extractant was passed through a clean-up syringe (pre-packed-with various sorbents including 500 mg anhydrous MgSO4, 50 mg C18, and 50 mg SiO2 ) to obtain the high order of matrice clean-up and preconcentration efficiency. The developed method displayed excellent linearity, and the correlation coefficients were >0.998 for all the target metabolites with detection and quantification limits of 0.02–0.24 ng mL −1 and 0.05–0.72 ng mL −1, respectively. Furthermore, the matrix effects were < ±5%, and inter and intra-day precision were <9%. Moreover, the presented method was applied and validated to real sample analysis for biomonitoring of VOC's exposure levels. The results showed that the developed FaUMEx-UHPLC-MS/MS method is fast, simple, low-cost, low-solvent consumption, high sensitivity with good accuracy and precision for five targeted urinary VOCs' metabolites. Therefore, the presented dual-syringe mode FaUMEx strategy with UHPLC-MS/MS technique can be applied to biomonitoring of various urinary metabolites to assess human exposure to environmental toxicants. Graphical abstract: Image 1 Highlights: Simultaneous biomonitoring of 5 volatile organic compounds' metabolites in human urine. A novel in-syringe based fast urinary metabolites extraction technique was developed. This method is a simple, fast, sensitive, low-cost, semi-automated and efficient protocol. This method can be applied to biomonitoring of various urinary metabolites. This method can be applied to assess human exposure to various environmental toxicants.